SYNTHESIS AND CHARACTERIZATION OF NOVEL ORGANOBISMUTH FOR ANTIMICROBIAL AND ANTITUMOR STUDIES - TRIPATHI, DIPTI MANI; KANT, RAVI; SRIVASTAVA, KRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The major objective of this manuscript is to present synthesis and biomedical screening of some organic derivatives of bismuth having general formula (R3BiL2) by the method reported and characterized with the help of M.P., elemental, I.R., and NMR spectral analysis along with their antimicrobial and in vitro antitumor activity against human breast (MCF-7) and mammary cancer (EVSA-7) cell line. Methods: All the newly organobismuth having general formula [R3BiL2] were synthesised by the method reported especially using oxidative addition and complexation reactions. Results: It was found that organobismuth compounds have trigonal bipyramidal structure as per their elemental and spectral analysis and show potentiality as antimicrobial and antitumor agents. Conclusion: The newly synthesized organobismuth(V)substituted carboxylates were fully characterized chemically to ascertain their structure by sophisticated instrumental and spectral analysis resulted as trigonal bipyramidal structure. The compounds were also screened 1st time for antitumor and antimicrobial studies. The observations clearly indicated that organobismuth carboxylates show potent antimicrobial and antitumor activity.